577. FDG PT-CT METABOLIC TUMOUR AND NODAL RESPONSE AS A PREDICTOR OF PATHOLOGICAL RESPONSE AND SURVIVAL IN PATIENTS WITH OESOPHAGEAL ADENOCARCINOMA. (24th September 2022) - Moore, Jonathan; Subesinghe, Manil; Santaolalla, Aida; Green, Michael; Deere, Harriet; Van Hemelrijck, Mieke; Lagergren, Jesper; Chicklore, Sugama; Maisey, Nick; Kelly, Mark; Gossage, James A; Baker, Cara R; et al.
Abstract: 2-deoxy-2[18F]fluoro-D-glucose positron emission tomography-computed tomography (FDG-PET-CT) is routinely used for staging of oesophageal cancer and has an emerging role in assessing response to neoadjuvant therapy. The primary aim of this study was to evaluate the ability of FDG-PET-CT to predict pathological response in the primary tumour (pTR) and lymph nodes (pNR) in patients with oesophageal adenocarcinoma undergoing neoadjuvant chemotherapy before surgery. The secondary aim was to assess the prognostic effect of metabolic and pathological response. Cohort study of 75 patients with locally advanced oesophageal or oesophago-gastric junctional adenocarcinoma who underwent FDG-PET-CT before and after neo-adjuvant chemotherapy, prior to surgical resection at a tertiary referral centre in the United Kingdom, between 2017-2020. Standardised uptake value (SUV) metrics related to the primary tumour and loco-regional lymph nodes were derived. pTR and pNR were evaluated using the Mandard classification. Receiver operator characteristic (ROC) analysis was performed and area under the curve (AUC) calculated to determine optimum SUVmax thresholds for metabolic response in the primary tumour (mTR) and lymph nodes (mNR). Survival was assessed using multivariable Cox regression. ROC analysis demonstrated an optimum tumour SUVmax decrease of 51.2% for predicting pTR. A pragmatic 50% cut-off provided better prediction of pTR (AUC 0.714, sensitivity 73.5%, specificity 69.2%, p<0.001) than PERCIST (30% reduction) and MUNICON (35% reduction) criteria. Using a 30% SUVmax threshold and excluding metabolically negative nodes, mNR demonstrated high sensitivity but low specificity (sensitivity 92.6%, specificity 57.1%, p=0.010) for predicting pNR. pTR, mTR, pNR and mNR were independent prognostic factors (pTR responder HR 0.10 95% CI 0.03-0.34; mTR responder HR 0.17 95% CI 0.06-0.48; pNR responder HR 0.17 95% CI 0.06-0.54; mNR responder HR 0.13 95% CI 0.02-0.66). Metabolic response predicted pathological response in both the primary tumour and lymph nodes in this cohort of patients with locally advanced oesophageal adenocarcinoma treated with neo-adjuvant chemotherapy. Metabolic tumour response, pathological tumour response, metabolic nodal response and pathological nodal response were all independent prognostic factors for survival. Currently utilised metabolic response criteria may not be optimal for this tumour group.